Preliminary Observtaions on Potential Water Requirement in Pinus roxburghii, Eucalyptus citriodora, Populus casale (488) and Dalbergia latifolia - Dabral, B. G. (Indian Forester, 1970)
Preliminary studies were made to determine the potential evapotranspiration using different forest species in juvenile stage. It was observed that Eucalyptus citriodora, Dalbergia latifolia, Pinus roxburghii and Populus casale in between 6-16, 6-16, 12-22 and 5-17 months of age consumed 16579/5526, 4570/1143, 1872/936 and 8112/2704 mm of water. The trend of water consumed for unit gram of dry matter production was least for Eucalyptus, and maximum for chirpine (Pinus roxburghii). Further work is necessary for conclusive results.